Carpal tunnel syndrome and manual work: the first 3 years of a longitudinal study. (19th October 2011) - Bonfiglioli, Roberta; Mattioli, Stefano; Armstrong, Thomas; Graziosi, Francesca; Marinelli, Francesco; Farioli, Andrea; Violante, Francesco
Abstract : Objectives: Evidence on occupational determinants of Carpal Tunnel Syndrome (CTS) mainly derived from cross-sectional or retrospective studies. We conducted a cohort study to investigate the association between biomechanical occupational exposures and CTS symptoms. Methods: A longitudinal study on different groups of industrial and service workers started in 2000; outcome measures were conducted after one and 2 years. Exposure assessment was conducted for each job task according to American Conference of Governmental Industrial Hygienists (ACGIH) recommendations; biomechanical loads were classified as: 1) below the Action Limit (AL); 2) between the AL and the Threshold Limit Value (TLV); 3) above the TLV. Case definition was based on self-reported symptoms of CTS and followed the Consensus Criteria for the Classification of CTS in Epidemiologic Studies. Results: After exclusions, 2472 workers entered our analyses. Subjects exposed between AL and TLV (adjusted IRR 2.33, 95% CI 1.76 to 3.07) and above TLV (adjusted IRR 3.07, 95% CI 2.33 to 4.05) showed an increased risk of CTS symptoms. However, while incidence of CTS symptoms dramatically increased by exposure status among females (adjusted incidence below the AL: 4.9/100 pyears, 95% CI 3 to 6.3; above the TLV: 17.7/100 pyears, 95% CI 12.8 to 22.7), a very small increase was found for males (adjusted incidence below the AL: 2.1/100 pyears, 95% CI 1.2 to 3.6; above the TLV: 3.8/100 pyears, 95% CI 2.1 to 6.7). Conclusions: We found a dose-response relationship between biomechanical exposure classified according to ACGIH and incidence of CTS symptoms. However, sex stratified analyses uncovered major differences between gender; these findings support the hypothesis that different exposure limits should be considered for males and females